Happiness Among Teenagers Who Have Parents as Migrant Workers: A Non-systematic Literature Review - Hantimart Yolanda Sevlywerty; Diana Aipipidely; Indra Yohanes Kiling (Universitas Nusa Cendana, 2021)
Adolescence is a period of transition from childhood to adulthood that affected many aspects of development. Adolescent’s happiness remains one of the relevant topics to be researched. Plenty of factors can bring happiness to teenagers, similarly many factors can make adolescents experience unhappiness, one of which is being separated from their parents for a long time for reasons of working abroad or becoming a TKI (Indonesian Migrant Worker). This literature review discusses happiness on teenagers in general and on teenagers who have parents working as migrant workers. Evidence showed that adolescents with parents as migrant workers need support as they are threatened by negative factors that make them as one of the most vulnerable children in Indonesia.